Effect of training on athropometric, physiological and biochemical variables of elite field hockey players - Manna, I.; Khanna, G. L.; Dhara, P. C. (International Journal of Sports Science and Engineering, 2010)
The aim of study was to investigate the effect of training on selected anthropometric, physiological and biochemical variables of elite field hockey players. A total of 30 Indian male field hockey players (age: 23.00-30.00 yrs) volunteered for this study. The training sessions were divided into 2 phases (a) Preparatory Phase (PP, 8 weeks) and (b) Competitive Phase (CP, 4 weeks). The training programme consist of aerobic, anaerobic and skill development, and were completed 4 hrs/day; 5 days/week. Selected variables were measured at zero level (baseline data, BD) and at the end of PP and CP. A significant increase (P<0.05) in LBM, back and hand grip strength, serum level of urea, uric acid and HDLC; and a significant decrease (P<0.05) in body fat, sub-maximal exercise heart rate and recovery heart rate, hemoglobin, total cholesterol, triglyceride and LDLC were noted in PP and CP of training when compare to BD. No significant change was noted in stature, body mass, HRmax, resting heart rate, VO2max and anaerobic power of the players after the training. Since the data on field hockey players are limited in India, the present study may provide useful information to the coaches to develop their training programme.